Usefulness of ultrasonography in diagnossis of hepatobiliary disease - Croci, Fabio; Petersen, Federico; Retich, Gizela; Arce, Enrique; Delgado, Bolívar (Cirugía del Uruguay, 1981)
Ultrasonography, which is a non-invasive method, has already preven considerable usefulness in the study of hepatobiliary and pancreatic disease